2011
DOI: 10.1111/j.1365-2761.2011.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Saprolegnia spp. to Atlantic salmon, Salmo salar L., eggs

Abstract: Live and dead Atlantic salmon eyed eggs were challenged with eight different Saprolegnia isolates, selected because of their varied origins, known morphological characteristics and growth/germination pattern. Some isolates were also tested for pathogenicity to Atlantic salmon parr. Challenge of eggs was performed by exposure to spores in suspension or by co-incubation of live eggs with infected dead eggs. The phenotypic characteristics of the isolates were evaluated in relation to their observed pathogenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 19 publications
3
53
1
3
Order By: Relevance
“…The observation that S. diclina sub-clade IIIB isolates also dominated in fected eggs (73%) seems natural considering the high overall prevalence in the hatchery water systems. It is also in concordance with Thoen et al (2011), who demonstrated through a challenge experiment that a presumed saprotrophic isolate was the single most pathogenic isolate to salmon eggs. Even though S. diclina is often believed to be a saprophytic species, our results may suggest that this species is responsible for a considerable portion of the eggs lost in saprolegniosis in Norway.…”
Section: Discussionsupporting
confidence: 89%
“…The observation that S. diclina sub-clade IIIB isolates also dominated in fected eggs (73%) seems natural considering the high overall prevalence in the hatchery water systems. It is also in concordance with Thoen et al (2011), who demonstrated through a challenge experiment that a presumed saprotrophic isolate was the single most pathogenic isolate to salmon eggs. Even though S. diclina is often believed to be a saprophytic species, our results may suggest that this species is responsible for a considerable portion of the eggs lost in saprolegniosis in Norway.…”
Section: Discussionsupporting
confidence: 89%
“…Padmakumar et al, (1985) found that fungal infected common carp eggs were enveloped with a cloudy cover and did not hatch and succumbed in 12-36 hrs. Thoen et al, (2011) noticed that the live egg contact with dead infected salmon egg had developed foci of white discoloration then death with total whitening. Saprolegnia species were grown on a surface of egg shell which affected it by direct adhesion mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is difficult to determine whether these species are opportunistic pathogens, or saprophytes that successfully colonized dead fish eggs that had died due to other causes. In the study of Thoen et al (2011), the ability of S. parasitica, S. diclina and Saprolegnia spp. isolates to successfully colonize and kill a live egg of Atlantic salmon was dependent on the quantity of inoculum and on the isolate tested.…”
Section: Discussionmentioning
confidence: 99%